Answer:
Step-by-step explanation:
The first 9 stands for 90,000 and the second for 9 000 so the first 9 is worth
90,000 / 9,000 equals 10 times the second one.
Answer:
The distance between house to work is 13 miles .
Step-by-step explanation:
Given as :
The distance that man travel to north = OA = 5 miles
Now, From north ,man turn right and travel to east
So, The distance that man travel to east = AB = 12 miles
Let The distance between house to work = x miles
So, x miles is the displacement from north to east direction
i.e x = ![\sqrt{OA^{2} + AB^{2} }](https://tex.z-dn.net/?f=%5Csqrt%7BOA%5E%7B2%7D%20%2B%20AB%5E%7B2%7D%20%20%7D)
Or, x = ![\sqrt{5^{2} + 14^{2} }](https://tex.z-dn.net/?f=%5Csqrt%7B5%5E%7B2%7D%20%2B%2014%5E%7B2%7D%20%20%7D)
Or, x = ![\sqrt{169 }](https://tex.z-dn.net/?f=%5Csqrt%7B169%20%20%7D)
∴ x = 13
So, The distance between house to work = x = 13 miles
Hence, The distance between house to work is 13 miles . Answer
Answer:
The solutions to the quadratic equations are:
![x=\sqrt{13}+3,\:x=-\sqrt{13}+3](https://tex.z-dn.net/?f=x%3D%5Csqrt%7B13%7D%2B3%2C%5C%3Ax%3D-%5Csqrt%7B13%7D%2B3)
Step-by-step explanation:
Given the function
![y\:=\:x^2\:-\:6x\:-\:4](https://tex.z-dn.net/?f=y%5C%3A%3D%5C%3Ax%5E2%5C%3A-%5C%3A6x%5C%3A-%5C%3A4)
substitute y = 0 in the equation to determine the zeros
![0\:=\:x^2\:-\:6x\:-\:4](https://tex.z-dn.net/?f=0%5C%3A%3D%5C%3Ax%5E2%5C%3A-%5C%3A6x%5C%3A-%5C%3A4)
Switch sides
![x^2-6x-4=0](https://tex.z-dn.net/?f=x%5E2-6x-4%3D0)
Add 4 to both sides
![x^2-6x-4+4=0+4](https://tex.z-dn.net/?f=x%5E2-6x-4%2B4%3D0%2B4)
Simplify
![x^2-6x=4](https://tex.z-dn.net/?f=x%5E2-6x%3D4)
Rewrite in the form (x+a)² = b
But, in order to rewrite in the form x²+2ax+a²
Solve for 'a'
2ax = -6x
a = -3
so add a² = (-3)² to both sides
![x^2-6x+\left(-3\right)^2=4+\left(-3\right)^2](https://tex.z-dn.net/?f=x%5E2-6x%2B%5Cleft%28-3%5Cright%29%5E2%3D4%2B%5Cleft%28-3%5Cright%29%5E2)
![x^2-6x+\left(-3\right)^2=13](https://tex.z-dn.net/?f=x%5E2-6x%2B%5Cleft%28-3%5Cright%29%5E2%3D13)
Apply perfect square formula: (a-b)² = a²-2ab+b²
![\left(x-3\right)^2=13](https://tex.z-dn.net/?f=%5Cleft%28x-3%5Cright%29%5E2%3D13)
![\mathrm{For\:}f^2\left(x\right)=a\mathrm{\:the\:solutions\:are\:}f\left(x\right)=\sqrt{a},\:-\sqrt{a}](https://tex.z-dn.net/?f=%5Cmathrm%7BFor%5C%3A%7Df%5E2%5Cleft%28x%5Cright%29%3Da%5Cmathrm%7B%5C%3Athe%5C%3Asolutions%5C%3Aare%5C%3A%7Df%5Cleft%28x%5Cright%29%3D%5Csqrt%7Ba%7D%2C%5C%3A-%5Csqrt%7Ba%7D)
solve
![x-3=\sqrt{13}](https://tex.z-dn.net/?f=x-3%3D%5Csqrt%7B13%7D)
Add 3 to both sides
![x-3+3=\sqrt{13}+3](https://tex.z-dn.net/?f=x-3%2B3%3D%5Csqrt%7B13%7D%2B3)
Simplify
![x=\sqrt{13}+3](https://tex.z-dn.net/?f=x%3D%5Csqrt%7B13%7D%2B3)
now solving
![x-3=-\sqrt{13}](https://tex.z-dn.net/?f=x-3%3D-%5Csqrt%7B13%7D)
Add 3 to both sides
![x-3+3=-\sqrt{13}+3](https://tex.z-dn.net/?f=x-3%2B3%3D-%5Csqrt%7B13%7D%2B3)
Simplify
![x=-\sqrt{13}+3](https://tex.z-dn.net/?f=x%3D-%5Csqrt%7B13%7D%2B3)
Thus, the solutions to the quadratic equations are:
![x=\sqrt{13}+3,\:x=-\sqrt{13}+3](https://tex.z-dn.net/?f=x%3D%5Csqrt%7B13%7D%2B3%2C%5C%3Ax%3D-%5Csqrt%7B13%7D%2B3)
I believe that you could factor (x+1) out of the polynomial